Midialivrismo e narrativas hegemônicas: uma cartografia de contranarrativas - Carvalho, Antônio Donizeti de (2020)
The present research examines the emergent processes in the communicational field and as narratives implemented by the new authors of the medialivrism as opposed to the narratives used by the traditional emitters of the institutional media. Therefore, critical analysis of recent events in Brazil is launched, such as street demonstrations from June 2013, a time when alternative forms of information become evident and interfere in the workflows of traditional media. Observing whether until the 2016 acts there was a polarization in the claims, before several, part for investigation of elements that can use this concretization, as well as, which agents and possible speeches, from command words, create consensus with a contract of Communication; that is, how to form an agglutination of the multiple claims that reverberated in the streets and that were lead to incorporate around the impeachment / coup of President Dilma Rousseff, having as a guiding element or echoed fight against corruption. This research promulgate the following question: Between what is silenced by the mainstream media and radiated by progressive websites, or even about what is overexposed by those vehicles, facts or personalities, and reworked by them, what is the dimension of this counter-narrative in order to establish a relativization of what is massively represented? From a cartography of the criticism offered by these new media to the performance of the mainstream Brazilian media, an analysis of the different narratives of the facts comprised in the corpus is developed. The thesis aims, therefore, to contribute to the field of communication making a historical documentation of this counter-narrative, and the existence of its vectors. The corpus includes vehicles belonging to the main communication groups in the country: the newspapers O Globo, Folha de S. Paulo, O Estado de S. Paulo; Veja magazine and Globonews and Rede Globo TV channels. A counterpart is created by websites and blogs that call themselves progressive and that emerge with the concept of free and collaborative media, with emphasis on: Jornal GGN, Diário do Centro de Mundo and Intercept Brasil. The theoreticalepistemological framework recovers authors such as: Érik Neveu (sociology of journalism); Fábio Malini, Henrique Antoun and Ivana Bentes (social media, cyberactivism and mobilization in networks); José Arbex Jr. (news as a show); Jessé Souza (reinterpretation of Brazil)